Heterologous Rhamnolipid Biosynthesis: Advantages, Challenges, and the Opportunity to Produce Tailor-Made Rhamnolipids - Wittgens, Andreas; Rosenau, Frank (Frontiers in Bioengineering and Biotechnology, 2020)
The first heterologous expression of genes responsible for the production of rhamnolipids was already implemented in the mid-1990s during the functional identification of the rhlAB operon. This was the starting shot for multiple approaches to establish the rhamnolipid biosynthesis in different host organisms. Since most of the native rhamnolipid producing organisms are human or plant pathogens, the intention for these ventures was the establishment of non-pathogenic organisms as heterologous host for the production of rhamnolipids. The pathogenicity of producing organisms is one of the bottlenecks for applications of rhamnolipids in many industrial products especially foods and cosmetics. The further advantage of heterologous rhamnolipid production is the circumvention of the complex regulatory network, which regulates the rhamnolipid biosynthesis in wild type production strains. Furthermore, a suitable host with an optimal genetic background to provide sufficient amounts of educts allows the production of tailor-made rhamnolipids each with its specific physico-chemical properties depending on the contained numbers of rhamnose sugar residues and the numbers, chain length and saturation degree of 3-hydroxyfatty acids. The heterologous expression of rhl genes can also enable the utilization of unusual carbon sources for the production of rhamnolipids depending on the host organism.